IMPLEMENTASI HAK KEKAYAAN INTELEKTUAL SEBAGAI JAMINAN HUTANG MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 2022 (Studi Pada Bank BRI Kantor Wilayah Bandar Lampung) - Erland Maulana; Erlina Bachri; Zainudin Hasan (INTELIGENSIA MEDIA, 2025)
Government Regulation Number 24 of 2022 concerning the Creative Economy has been issued by the government in order to provide facilities and solutions to Creative Economy actors, to maintain economic rights to a work from their Intellectual Property results that can be used as collateral for debt to bank or non-bank financial institutions, and is expected to overcome financing problems for the actors. The purpose of this writing is to find out the requirements and implementation of the Intellectual Property-based financing scheme that can be used as collateral for debt. The method used in this study is normative juridical, namely legal research by inventorying and reviewing laws and regulations, legal documents, and other written works and their application to legal events related to Intellectual Property and the Creative Economy. The data analysis used is qualitative juridical, namely by providing an understanding of the data in question according to the facts obtained in the field, which are arranged in the form of descriptive sentences so that they are truly answers to the existing problem. The problem in this study is the requirements and implementation of Intellectual Property Rights as collateral for debt according to Government Regulation Number 24 of 2022 concerning the Creative Economy at Bank BRI Bandar Lampung Regional Office. The results of this study indicate that in the submission of Intellectual Property-Based Financing, in Government Regulation Number 24 of 2022 concerning the Implementing Regulations of Law Number 24 of 2019 concerning the Creative Economy, the requirements for submitting loan collateral with Intellectual Property collateral are clearly stated. The implementation of Intellectual Property-Based Financing in Indonesia, despite being stated in the regulations, there are still many obstacles in the objective conditions in the field that must be faced by Creative Economy Actors, such as the role of the government in maximizing or realizing things that are already in the regulations related to the Creative Economy, and the awareness of the Creative Economy Actors themselves in developing Creative Economy businesses.